2019
DOI: 10.1002/jso.25480
|View full text |Cite
|
Sign up to set email alerts
|

A novel online prognostic tool to predict long‐term survival after liver resection for intrahepatic cholangiocarcinoma: The “metro‐ticket” paradigm

Abstract: Background The aim of the current study was to develop an online calculator to predict survival after liver resection for intrahepatic cholangiocarcinoma (ICC) based on the “metro‐ticket” paradigm. Methods Between 1990 and 2016, patients who underwent liver resection for ICC were identified in an international multi‐institutional database. The final multivariable model of survival was used to develop an online prognostic calculator of survival. Results Among 643 patients, actual 5‐year overall survival (OS) af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Our results also suggested that solitary ICC was a heterogeneous group, and larger tumor size was associated with malignant pathological factors, including worse tumor differentiation ( 20 , 22 ) and VI ( 20 , 24 ). It was believed that a larger tumor size was associated with various malignant variables ( 25 28 ).…”
Section: Discussionsupporting
confidence: 65%
“…Our results also suggested that solitary ICC was a heterogeneous group, and larger tumor size was associated with malignant pathological factors, including worse tumor differentiation ( 20 , 22 ) and VI ( 20 , 24 ). It was believed that a larger tumor size was associated with various malignant variables ( 25 28 ).…”
Section: Discussionsupporting
confidence: 65%
“…Several recent studies have suggested a 'metroticket' paradigm to evaluate survival [12][13][14][15][16]. This paradigm was originally proposed by Mazzaferro et al for hepatocellular cancer (HCC) and later evolved into a novel predictive tool for HCC patients after liver transplantation [12].…”
Section: Ivyspring International Publishermentioning
confidence: 99%
“…Based on the concept of the metro-ticket paradigm for gastric cancer, we proposed the current nTNM classification by combining the pN and pT stages, with preserved definitions of pN and pT stages. The nTNM was defined as the distance from the origin on a Cartesian plane that incorporated two variables: the pN stage (x-axis) and pT stage (y-axis); Pythagoras theorem was then used to calculate the distance of any given point from the origin of the plane (0, 0), where [(nTNM) 2 = (pN) 2 + (pT) 2 ] (Figure 1A, 1B) [12][13][14][15][16]. The nTNM classification was similar to the AJCC classification and was divided into seven subgroups: I, IIA, IIB, IIC, IIIA, IIIB, and IIIC.…”
Section: Development Of Ntnm Staging Systemmentioning
confidence: 99%
“…Indeed, depending on the size and location of iCCA lesions, curative resection may require extensive resection and/or resection of the extrahepatic biliary tract, a condition that may occur in many cases. In a large surgical series, 50-70% of patients required either a hemihepatectomy or extended hepatic resection [30] . The removal of clinically suspicious nodal disease is mandatory, while the role of routine lymphadenectomy is less defined, although it is current practice in many Japanese centers [1][2][3][4] .…”
Section: Surgerymentioning
confidence: 99%